Die Instituut vir Reformatoriese Studie (1962-1999) as Christelike organisasie – die betekenis daarvan vir toekomstige Christelike aksies - Walt, Barend Johannes van der (Koers, 2006)
The Institute for Reformational Studies (1962-1999) as a Christian organisation – its relevance for future Christian actions During a period of 37 years the Institute for Reformational Studies (IRS) fulfilled a unique role at the former Potchefstroom University for Christian Higher Education. In spite of this, the IRS was closed down at the end of 1999. This happened while, in an increasingly secularised South Africa, there clearly is a growing need to provide direction in all domains of life. This article, therefore, asks the question about possible reasons for the termination of this Institute. The answer to the problem is given from a worldview perspective. The aim of the investigation is to provide, derived from the history of the IRS, some practical guidelines to future Christian actions.